ANALISIS FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV MADRASAH IBTIDAIYAH NEGERI 3 INDRAMAYU - Laily, Alifa Nur; Peranginangin, Henri; Mardani, Dadan (Komunitas Manajemen Kompetitif, 2023)
This research aims to determine the learning difficulties experienced by students in class mathematics learning, to find out the causes of students' difficulties in learning mathematics in class, to reveal efforts that can be made to overcome class IV mathematics learning difficulties at Madrasah Ibtidaiyah Negeri 3 Indramayu. The data source for this research is class IV of Madrasah Ibtidaiyah Negeri 3 Indramayu. This data was collected using research instruments in the form of observations and interviews. The data analysis technique in this research uses descriptive qualitative. The research results show that first, the factors causing learning difficulties for class IV students of Madrasah Ibtidaiyah Negeri 3 Indramayu in mathematics subjects come from internal and external factors, namely that the majority of students tend to perceive that mathematics lessons are difficult or difficult. Second, the methods used by teachers in teaching mathematics have not fully attracted students' enthusiasm for learning mathematics. Third, the teaching efforts made in mathematics lessons are using concrete and fun learning media, increasing practice, and collaborating with students' guardians or parents.